Glucodynia - Sanjay Kalra; Navneet Agrawal; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
Pain in patients with diabetes can be unpleasant, but at times protective as well. We propose the term ‘glucodynia’ i.e., an unpleasant sensory and emotional experience, associated with or without any organ-system dysfunction, in people living with diabetes. Glucodynia may be due to microvascular, musculoskeletal, metabolic, mood-related, miasmatic, mitogenic, visceral myogenic, malnutritionrelated or medicine-related (iatrogenic) causes. In this manuscript we explain the different mechanisms of pain in patients living with diabetes. Furthermore, the therapeutic modalities that can be used to reduce pain sensation are described. Keywords: Diabetic neuropathy, glucodynia, pain, paresthesia, person centered